Intermittent fasting and neurodegenerative diseases: molecular mechanisms and therapeutic potential - Lv, Renjun; Liu, Bin; Jiang, Ziying; Zhou, Runfa; Liu, Xiaoxing; Lu, Tangsheng; Bao, Yanping; Huang, Chunxia; Zou, Guichang; Zhang, Zongyong; Lu, Lin; Yin, Qingqing (Metabolism, 2025)
Neurodegenerative disorders are straining public health worldwide. During neurodegenerative disease progression, aberrant neuronal network activity, bioenergetic impairment, adaptive neural plasticity impairment, dysregulation of neuronal Ca2+ homeostasis, oxidative stress, and immune inflammation manifest as characteristic pathological changes in the cellular milieu of the brain. There is no drug for the treatment of neurodegenerative disorders, and therefore, strategies/treatments for the prevention or treatment of neurodegenerative disorders are urgently needed. Intermittent fasting (IF) is characterized as an eating pattern that alternates between periods of fasting and eating, requiring fasting durations that vary depending on the specific protocol implemented. During IF, depletion of liver glycogen stores leads to the production of ketone bodies from fatty acids derived from adipocytes, thereby inducing an altered metabolic state accompanied by cellular and molecular adaptive responses within neural networks in the brain. At the cellular level, adaptive responses can promote the generation of synapses and neurons. At the molecular level, IF triggers the activation of associated transcription factors, thereby eliciting the expression of protective proteins. Consequently, this regulatory process governs central and peripheral metabolism, oxidative stress, inflammation, mitochondrial function, autophagy, and the gut microbiota, all of which contribute to the amelioration of neurodegenerative disorders. Emerging evidence suggests that weight regulation significantly contributes to the neuroprotective effects of IF. By alleviating obesity-related factors such as blood-brain barrier dysfunction, neuroinflammation, and β-amyloid accumulation, IF enhances metabolic flexibility and insulin sensitivity, further supporting its potential in mitigating neurodegenerative disorders. The present review summarizes animal and human studies investigating the role and underlying mechanisms of IF in physiology and pathology, with an emphasis on its therapeutic potential. Furthermore, we provide an overview of the cellular and molecular mechanisms involved in regulating brain energy metabolism through IF, highlighting its potential applications in neurodegenerative disorders. Ultimately, our findings offer novel insights into the preventive and therapeutic applications of IF for neurodegenerative disorders.
Online verfügbar: 12. Dezember 2024, Artikelversion: 21. Dezember 2024
Gesehen am 15.05.2025